2022
DOI: 10.1002/ps.6908
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses reveal regional structure and demographic expansion of the predominant tea pest Empoasca onukii (Hemiptera: Cicadellidae) in China

Abstract: BACKGROUND: The tea green leafhopper, Empoasca onukii Matsuda, is the most destructive insect pest of tea plantations in East Asia. Despite its economic importance and previous studies on this species, it remains unclear as to how this small-sized pest can have such wide range. RESULTS: By sequencing three mitochondrial genes and 17 microsatellite loci, we revealed the regional structure and demographic expansion of 59 E. onukii populations in China. Bayesian analysis of population genetic structure (BAPS) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 93 publications
1
9
0
Order By: Relevance
“…These results are supported by the cold‐adaptive biological characteristics of P. horticola and reinforce the inference that the P. horticola population expanded during the LGM. Although many regions may become unsuitable for P. horticola in the future, studies have shown that the expansion of host‐plant cultivation areas and centres of frequent crop trade have contributed to the expansion of pest populations, including those of Empoasca onukii and Frankliniella occidentalis (Cao et al, 2017; Li et al, 2022; Reitz et al, 2020). Therefore, to prevent and control P. horticola in the future, the focus should be on cold areas at high latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by the cold‐adaptive biological characteristics of P. horticola and reinforce the inference that the P. horticola population expanded during the LGM. Although many regions may become unsuitable for P. horticola in the future, studies have shown that the expansion of host‐plant cultivation areas and centres of frequent crop trade have contributed to the expansion of pest populations, including those of Empoasca onukii and Frankliniella occidentalis (Cao et al, 2017; Li et al, 2022; Reitz et al, 2020). Therefore, to prevent and control P. horticola in the future, the focus should be on cold areas at high latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The species occurrence records of tea were obtained from a previous study on the global climatic suitability of tea (Zhang et al, 2019b). In contrast, occurrence records for the tea green leafhopper were sourced from three distinct channels: (1) field sampling (Li et al, 2022), (2) published literature (Li et al, 2013;Fu et al, 2014a;Fu et al, 2014b;Zhou et al, 2014;Chen et al, 2015;Zhang et al, 2019a), and (3) the Global Biodiversity Information Facility (GBIF.org). Due to the use of various scientific names for the tea green leafhopper in prior studies, such as E. flavescens, E. pirisuga, Jacobiasca formosana, E. vitis, and E. onukii (Qin et al, 2015), all of these names were employed to compile the occurrence records for the tea green leafhopper.…”
Section: Study Area and Species Occurrence Recordsmentioning
confidence: 99%
“…Furthermore, considering the field activity characteristics of leafhoppers, the direct impact of precipitation on leafhopper populations can be limited. Female adults of tea green leafhopper lay their eggs in tender tea shoots and leaves, and both the adults and nymphs often seek shelter behind the tender leaves, where they feed on the sap (Li et al, 2022). In this context, tender tea shoots and leaves can help leafhopper populations avoid or alleviate the unfavorable influence of precipitation, resulting in a lesser role for precipitation compared to temperature in driving leafhopper habitat use.…”
Section: Environment Driver Of Habitat Usementioning
confidence: 99%
See 1 more Smart Citation
“…Adult females also lay their eggs in these shoots, leading to irreparable damage ( 13 ). Matsumurasca onukii can cause yield losses of between 15% and 50%, and up to 100% in severely damaged plantations ( 14 ). More importantly, M. onukii is well adapted to different tea varieties and geographical variations ( 15 ).…”
Section: Introductionmentioning
confidence: 99%